Unknown syndrome: microcephaly, hypoplastic nose, exophthalmos, gum hyperplasia, cleft palate, low set ears, and osteosclerosis. - Raine, J (1989)
We report a neonate, born at term, with microcephaly, a hypoplastic nose, exophthalmos, gum hyperplasia, cleft palate, and low set ears, who died at 86 minutes of age. Radiographs showed diffuse sclerosis of the bones.